Kemandirian Ekonomi Sekolah Melalui Penyelenggaraan Pembelajaran Berbasis Pabrik (Teaching Factory) di SMKS Islam YPI 2 Way Jepara Lampung Timur - Kurniawan Kurniawan (Invention: Journal Research and Education Studies, 2026)
This research discusses economic independence through teaching factory as an effort to address the low absorption rate of vocational high school graduates. The researcher used a descriptive qualitative approach with a case study method, involving interviews, observations, and documentation in data collection. The results of the study show that teaching factory learning in schools, besides providing a learning atmosphere based on industry, can have a positive impact on schools regarding economic independence, including: School Budget Efficiency, Economic Added Value, and stimulating a multiplier effect for the growth of local creative industry areas. This study concludes that schools can replicate teaching factory learning for the economic independence of the school.